ГОТОВНІСТЬ УЧИТЕЛІВ ГЕОГРАФІЇ СПЕЦІАЛЬНИХ ШКІЛ СЛОВАЦЬКОЇ РЕСПУБЛІКИ ДО ВИКОРИСТАННЯ ЕЛЕКТРОННОГО ДИДАКТИЧНОГО ПОСІБНИКА З IT-ПІДТРИМКОЮ - Гладуш, Віктор; Ковачова, Барбора; Бендікова, Славка; Чарницька, Марцела (Information technologies and learning tools, 2024)
The purpose of the article is to highlight the level of readiness of teachers of geography of special schools of the Slovak Republic (on the example of 14 of special and inclusive education institutions of the Košice Region) to the use of an electronic didactic manual on IT support. Teachers of the Department of Special Pedagogy of the Pedagogical Faculty of the Catholic University in Ruzomberok together with teachers of the geography of special schools prepared an electronic didactic manual on IT support taking into account modern requirements to the level of knowledge, abilities and psychophysical capabilities of school children with special education needs. The manual has helped to raise the level of geographical learning among school children of special school. The convincing results of the pedagogical experiment are described in the previous article «Using a didactic tool with IT-support for teaching geography in a special school in Slovakia». However, in the course of studying the question the researchers concluded that success in the work depends on the level of readiness of the teacher for this work. Namely, the presence of interest and motivation to the introduction of innovative forms of training for the subjects of the education process the attitude of the teacher to the organization of the education process, the level of professional training (possession of the means and technologies of training). To obtain objective and unbiased results Google Form has conducted a survey of  teachers of geography. The first set of questions – the reference one – provided an opportblocky to explain the answers of the second set of questions – the informative one. The statistical processing of the survey results supports the assumption that the quality of the IT-supported e-manual is largely dependent on the teacher’s readiness. The results also show that the majority of  teachers of geography surveyed are well aware of the benefits of this teaching tool and are now ready to put the manual into practice. However, due to the rapid progress in the use of information and communication technologies the teachers of special schools do not deny the need to improve their professional knowledge of the use of ICT in postgraduate teacher training. Метою статті є висвітлення рівня готовності вчителів географії спеціальних шкіл Словацької республіки (на прикладі 14 закладів спеціальної та інклюзивної освіти Кошицького краю) до застосування електронного дидактичного посібника з ІТ-підтримкою. Викладачами кафедри спеціальної педагогіки Педагогічного факультету Католицького університету в Ружомберку спільно з вчителями географії спеціальних шкіл підготовлено електронний дидактичний посібник з ІТ-підтримкою з урахуванням сучасних вимог до рівня знань, умінь та психофізичних можливостей учнів з порушеннями інтелектуального розвитку. За допомогою посібника вдалося підвищити рівень оволодіння географічними знаннями учнів спеціальних шкіл. Переконливі результати педагогічного експерименту описані в попередній статті «Using a didactic tool with IT-support for teaching geography in a special school in Slovakia». Утім у ході вивчення питання дослідники дійшли висновку, що успіх у роботі вагомо залежить від рівня готовності вчителя до цієї роботи. А саме від наявності у суб’єктів освітнього процесу інтересу та мотивації до запровадження інноваційних форм навчання, ставлення вчителя до організації освітнього процесу, рівня професійної підготовки (володіння засобами та технологіями навчання). Для отримання об’єктивних та неупереджених результатів за допомогою Google Form проведено опитування вчителів географії. Перший блок питань – довідковий, за допомогою цих відповідей з'явилась можливість пояснювати відповіді другого блоку – інформаційного. Статистична обробка результатів опитування підтверджує припущення про те, що якість використання електронного посібника з ІТ-підтримкою багато в чому залежить від рівня готовності вчителя. Результати також свідчать, що переважна більшість опитаних учителів географії добре розуміють переваги цього засобу навчання і сьогодні вже готові на практиці застосовувати посібник у педагогічній практиці. Утім через стрімкий прогрес у використанні інформаційно-комунікаційних засобів, які мають необмежені можливості, педагогічні працівники спеціальних шкіл розуміють потребу в удосконаленні своїх професійних знань з використання ІКТ у системі післядипломної педагогічної освіти.